2008
DOI: 10.1200/jco.2007.12.5807
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of a Toll-Like Receptor 9 Agonist Oligodeoxynucleotide, PF-3512676, in Combination With First-Line Taxane Plus Platinum Chemotherapy for Advanced-Stage Non–Small-Cell Lung Cancer

Abstract: The addition of PF-3512676 to taxane plus platinum chemotherapy for first-line treatment of NSCLC improves objective response and may improve survival. Confirmatory phase III trials are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 39 publications
1
100
1
1
Order By: Relevance
“…Phase I and II clinical trials have indicated that these agents have antitumor activity as single agents and enhance the development of antitumor T cell responses when used as therapeutic vaccine adjuvants (26)(27)(28)(29)(30). In another phase II study of TLR9 agonist oligodeoxynucleotide in combination with first-line taxane plus platinum chemotherapy in the treatment of advanced-stage non-small-cell lung cancer, the author concluded that addition of PF-3512676, a TLR9 agonist, to taxane plus platinum chemotherapy for first-line treatment of NSCLC improves objective response and may improve even survival of patients (31). It may be only a result of the chemosensitization effect of TLR9 agonist by upregulating antitumor activity of immunocells.…”
Section: Discussionmentioning
confidence: 99%
“…Phase I and II clinical trials have indicated that these agents have antitumor activity as single agents and enhance the development of antitumor T cell responses when used as therapeutic vaccine adjuvants (26)(27)(28)(29)(30). In another phase II study of TLR9 agonist oligodeoxynucleotide in combination with first-line taxane plus platinum chemotherapy in the treatment of advanced-stage non-small-cell lung cancer, the author concluded that addition of PF-3512676, a TLR9 agonist, to taxane plus platinum chemotherapy for first-line treatment of NSCLC improves objective response and may improve even survival of patients (31). It may be only a result of the chemosensitization effect of TLR9 agonist by upregulating antitumor activity of immunocells.…”
Section: Discussionmentioning
confidence: 99%
“…Although at least nine distinct TLRs have been discovered in mammals (62), drug development efforts have focused on targeting TLRs 3, 7, and 9, because they are thought to effectively integrate innate and adaptive immune responses (63). However, the promise of such TLR agonist-based therapies has not been borne out in the clinic, not only because little attention has been paid to identifying the most suitable target tumor types, but also because systemic administration of the pharmacologics used to engage these particular TLR pathways have led to "cytokine storm"-related dose-limiting toxicities (10)(11)(12). This led us to consider that the therapeutic value of the "TLR agonist concept" might be markedly improved by exploiting a TLR system intrinsic to the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Although proof-ofprinciple for this concept has been demonstrated with agonists of several TLRs (TLR3, -7, and -9) (8), only one, the TLR7 agonist Imiquimod, has been approved for clinical use [however, this is limited to topical treatment of basal cell carcinoma (9)]. The major clinical limitations of many TLR agonists are the risk of dose-limiting toxicities associated with their systemic delivery (10)(11)(12) and metastasis stimulation (13)(14)(15). Furthermore, some previously investigated TLR agonists are restricted to injection directly into tumor tissue (3,(16)(17)(18), an approach that will likely have limited therapeutic value in cancer patients with metastatic disease.…”
mentioning
confidence: 99%
“…Statistical analysis suggests a trend toward improved survival for patients treated with ODN plus chemotherapy. The median survival for patients in the ODN plus chemotherapy arm was 12.3 months compared with 6.8 months for patients in the chemotherapy-alone group [124].…”
Section: Tlrs In Clinical Trials Against Human Malignanciesmentioning
confidence: 99%